Design and Implementation of Pulse Width Modulation Using Hardware/Software MicroBlaze Soft-Core - A. Zemmouri; R. Elgouri; M. Alareqi; M. Benbrahim; L. Hlou (Institute of Advanced Engineering and Science, 2017)
This paper presents an embedded control application of clock frequency to control the pulse width of the output signals, implemented on field programmable get array. This control allows the creation of lines of Pulse-width modulation depending on the numbers of card outputs, without using the specific